EVALUATION OF EFFICIENCY IN THE PUBLIC SECTOR - Žubule, Ērika; Kavale, Lūcija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper is focused on the efficiency of government activities and possibilities of evaluating it. Nowadays an appropriate use of public finances is an urgent problem of financial management of the state. Therefore, a special emphasis is put on the necessity to evaluate the results of activities of the public sector. These results have become an important element of the public financial system oriented towards results, as they form a stable base for planning and evaluating government budget resources. Being unaware of results, it is impossible to estimate if the aims and tasks set by the government financial policy are real and appropriate to the current situation and financial resources. Therefore a systematic approach to the evaluation of activities of the state administration is necessary. It can be done with the help of the system of efficiency indicators.Existing views on efficiency evaluation options for the public sector in economic literature are summarized, related issues are highlighted and trends in the improvement of the performance indicators system are identified in the research.